Real-world treatment patterns and disease burden in generalized myasthenia gravis patients receiving non-steroidal immunosuppressants within the Brazilian public health system: a claims database study - Acary Souza Bulle Oliveira; Marcondes Cavalcante França; Paulo Victor Sgobbi Souza; Ligia Coelho; Gabriela Kanevsky; Julio Cesar Barbour Oliveira; Caroline Tianeze de Castro; Renato Watanabe de Oliveira (BMC Neurology, 2026)
Abstract Background Generalized myasthenia gravis (gMG) is a chronic autoimmune disorder affecting patients and healthcare systems. Limited real-world data exist on clinical journey and outcomes of patients with gMG within the Brazilian public health system (SUS). This study aimed to describe clinical profiles, treatment patterns, and healthcare resource use of patients with gMG receiving non-steroidal immunosuppressive therapy (NSIST) in SUS. Methods This retrospective cohort study used DATASUS database claims data (2013–2023). Adults with gMG who initiated NSIST were assessed. Primary outcomes were treatment patterns, including therapeutic sequences and dosage adjustments. Secondary outcomes included exacerbation rates, myasthenic crises, and healthcare resource utilization, stratified by treatment line and patients. Results The study included 1,207 patients on NSIST, of whom 17.65% had severe gMG. The cohort was predominantly female (66.5%) with early-onset disease (62.6%). Azathioprine was the most common first immunotherapy (90.1%). Patients on the second immunotherapy had double the number of exacerbations (25.62 vs. 13.54 per 100 person-years [PY]) and crises (2.31 vs. 0.74 per 100 PY) than those on the first NSIST. Hospitalization and ICU admission rates also increased significantly. NSIST-treated severe gMG patients showed the highest observed clinical burden. Conclusions Among NSIST-treated patients with gMG in the SUS, the disease imposed a substantial burden on both patients and the healthcare system, especially those requiring treatment escalation. These real-world findings offer descriptive evidence on the treatment patterns, clinical events, and healthcare resource use of NSIST-treated patients with gMG in the SUS and help identify the subgroups with the highest observed clinical and healthcare burden within this population.